Acceptability and participation predictors for a pragmatic randomized controlled trial to test a smoking cessation intervention after discharge from mental health wards. (1st May 2022) - Martínez, Cristina; Feliu, Ariadna; Torres, Núria; Nieva, Gemma; Pinet, Cristina; Raich, Antònia; Mondon, Sílvia; Barrio, Pablo; Andreu, Magalí; Hernández-Ribas, Rosa; Vicens, Jordi; Costa, Sílvia; et al.
Abstract: Background and Aim: Hospitalization is an ideal time to promote smoking cessation, but interventions are limited for supporting cessation maintenance after discharge. This study aimed to evaluate the acceptability of participating in a trial that tested the efficacy of an intensive telephone-based intervention for smokers after discharge. Methods: Adult smokers admitted to mental health wards of six hospitals were invited to participate in the trial. We studied the study acceptance/decline rates by analyzing the characteristics of participants (e.g., sex, age, psychiatric disorder, smoking pattern) and hospitals (e.g., size, tobacco control implementation). We calculated adjusted odds ratios (aOR) to assess predictors of non-participation. Results: Of 530 smokers that met the study inclusion criteria, 55.5% (n = 294) agreed to participate. Participant and non-participants were not different in sex, age, or psychiatric diagnosis. Compared to non-participants, participants had made more attempts to quit in the past year (66.1% vs 33.9%; p < 0.001) and reported higher abstinence rates during the hospital stay (66.7% vs. 33.3%; p = 0.05). Participation rates by hospital varied from 30.9% to 82.0% (p < 0.001). Predictors of non-participation were not having attempted to quit in the last year (aOR=2.42; 95%CI: 1.66–3.53) and low level of tobacco control in the hospital (aOR range: 1.79–6.39, p < 0.05). Conclusions: A telephone-based intervention to promote smoking cessation after discharge was accepted by half of the smokers with mental health disorders. Smokers that had attempted to quit previously and those that stayed in hospitals with a strong tobacco control policy were more likely to participate in the trial. Highlights: 50% of smokers with mental health disorders accepted a quit-smoking intervention. Smokers that had attempted to quit were more likely to participate in the trial. Hospital tobacco control policies mediated participation rates. A quitline program may promote cessation benefits introduced during hospitalization.